Analisis Faktor yang Mempengaruhi Minat Tenaga Kerja Wanita Bekerja di PTPN X Unit Industri Bobbin Kecamatan Arjasa Kabupaten Jember - Maktubatul Hasanah; P. Edi Suswandi; Duwi Yunitasari (UPT Penerbitan Universitas Jember, 2019)
Jember Regency is the best tobacco producing region in the world and absorbs female workers. The purpose of this study was to analyze the variables of income, age, education and the number of dependents on the interest of female workers working at PTPN X Industrial Unit Bobbin. The analytical method used is Ordinary Least Squares (OLS) and the model used by Binary Logistic Regression using primary data which includes data on labor decisions, income, age, education and number of dependents. Samples taken were 100 respondents. Sampling was calculated using the proportional stratified random sampling formula. The results showed that income, age, education had a negative and significant effect, while the number of dependents did not affect the interest of female workers working at PTPN X Bobbin Industrial Unit. Keywords: Interest of female workers, Income, Age, Education, Family members.